Clinical challenge: a case of testicular tumor disguised as a prenatal testicular torsion - Ioana Fugaru; Joseph Moryousef; Van-Hung Nguyen; Mohamed El-Sherbiny (SpringerOpen, 2023)
Abstract Background Neonatal tumors account for a minority of prepubertal testicular tumors. Similarly, testicular torsion in the neonate within the intrauterine or postnatal period is a rare event with an estimated incidence of 6 per 100,000. Testicular salvage is almost never achieved in cases of prenatal testicular torsion and there is still no consensus on the ideal management. Case presentation A neonate with prenatal testicular torsion that underwent inguinal orchiectomy. On pathological examination, an uncharacterizable, multicystic, and well-delineated testicular tumor was identified. Although rare, testicular tumor presenting as neonatal testicular torsion should be considered in the differential diagnosis of an acute neonatal scrotum. Conclusions This case highlights that an inguinal approach for surgical exploration in prenatal testicular torsions may be preferred given the risk, albeit extremely low, of an underlying testicular tumour.